A STUDY ON MACROECONOMIC AGGREGATES IN INDIA (2016-17 TO 2022-23) - G.N., Ramakrishna (International Journal of Research -GRANTHAALAYAH, 2024)
This abstract presents a succinct summary of the main insights and discoveries obtained from a dataset of macroeconomic aggregates in India covering the period from 2016-17 to 2022-23. The data presents a number of noteworthy patterns, such as a consistent upward trajectory in population figures, as well as sustained expansion in both Gross Domestic Product (GDP) and Gross National Income (GNI). The per capita income indicators also demonstrate a positive trend, indicating an enhancement in living standards. The levels of savings and capital formation have exhibited variability throughout the years, underscoring the imperative of implementing stable economic policies that foster investment. In addition, it is crucial to emphasize the significance of prompt and precise data collection and reporting in order to facilitate informed decision-making, as evidenced by the tentative nature of the data for the period of 2022-23. In summary, the aforementioned findings offer valuable insights for policymakers and analysts, underscoring the importance of implementing inclusive economic policies, ensuring economic stability, and consistently improving data collection and analysis to steer India's economic advancement.